Design Aesthetics: Theoretical Basics and Studies in Implication - Folkmann, Mads Nygaard (The MIT Press, 2023)
An original exploration of the role of aesthetics in contemporary design, uniquely combining philosophical aesthetics and cultural analysis of design.As a product of human ingenuity, design functions as an artificial interface through which we meet the world. While the ubiquity of design seems to render it imperceptible, when we truly reflect on design, we see that it is inextricably entwined with our experience of the world. In Design Aesthetics, Mads Nygaard Folkmann provides an engaging introduction to the field of design aesthetics and its role as a concept. Engaging with sensual, conceptual, and contextual considerations of design aesthetics, this book investigates design experience in tandem with design practice, objects, and perception. Part one of Design Aesthetics lays the theoretical foundation by differentiating between sensual, conceptual, and contextual dimensions of design aesthetics and clarifying what “aesthetic experience” means in relation to design. The second part of the book consists of studies in implications of design aesthetics for design practice, design objects with embedded technology, and the construction of perception of aesthetic qualities in objects. In its focus on design aesthetics, the book is intended for everyone working with design—design students, designer researchers, and designers—as well as students and researchers in aesthetics in general.